STUDY OF ONLINE BUYING INTENTION STUDY OF “ ONLINE SHOPPING” - Yuliana, Rahmi; Hamdani, Muliawan (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
This study is to determine how the influence of online brand image, service standard communication, word of mouth on Brand Commitment on Shopee's online shop site in Semarang City and the influence of Brand Commitment on Online Buying Intention. The sampling technique used in this study was a snowball using the Slovin formula as many as 100 people. The data collection method used was a questionnaire distributed online. In this study, online buying intention, service standard communication, word of mouth are significantly influenced by brand commitment. Brand commitment is the mediation of the influence of online brand image, service standard communication and word of mouth on online buying intentions. Keywords: online brand image, service standard communication, word of mouth, brand commitment